Sistem Presensi Karyawan Berbasis Face Recognition di Koperasi Gudang Pusat TNI AD - Rieziq, Farid; Sancoko, Sulistyo Dwi (STMIK Banjarbaru, 2024)
This study examines the application of facial recognition technology to enhance employee performance at the TNI AD Central Warehouse Cooperative. Conventional attendance methods are prone to fraud and inefficiency. The proposed solution is a facial recognition-based attendance system that records attendance automatically and in real-time, improving security and operational efficiency. The study follows the waterfall system development method, covering requirements analysis to testing, with black box testing results showing a 100% success rate for all application functions, operating according to specifications without issues. The testing outcomes demonstrate that the system simplifies the attendance process, prevents fraud, and facilitates leave or permission management, with additional features such as geolocation and QR codes that support more effective human resource management.Keywords: Attendance; Face Recognition; Geolocation; QR CodeÂ AbstrakPenelitian ini membahas penerapan teknologi face recognition untuk meningkatkan kinerja karyawan di Koperasi Gudang Pusat TNI AD. Metode presensi konvensional memiliki potensi terjadi kecurangan dan inefisiensi. Solusi yang diusulkan adalah sistem presensi berbasis face recognition yang mencatat kehadiran secara otomatis dan real-time, meningkatkan keamanan dan efisiensi operasional. Penelitian ini mengikuti metode pengembangan sistem waterfall dari analisis kebutuhan hingga pengujian, dengan hasil pengujian black box yang menunjukkan tingkat keberhasilan 100% pada seluruh fungsi aplikasi, berjalan sesuai spesifikasi tanpa kendala. Hasil pengujian menunjukkan bahwa sistem ini mampu mempermudah proses presensi, mencegah kecurangan, dan mempermudah pengelolaan izin atau cuti, dengan fitur tambahan seperti geolocation dan QR code yang mendukung pengelolaan sumber daya manusia secara lebih efektif.Â